Research progress of enamel matrix derivative on periodontal tissue regeneration: a narrative review - Xiang, Chenyang; Zhang, Linglin; Tao, Enfu (Frontiers in Dental Medicine, 2025)
Extensive research has demonstrated that enamel matrix derivative (EMD) facilitates periodontal tissue regeneration, enabling the genuine regeneration of cementum, periodontal ligament, and alveolar bone. Its clinical formulation, Emdogain, is currently employed in the treatment of alveolar bone defects resulting from periodontitis, as well as in dental implantation and tooth replantation procedures. This review aims to synthesize recent findings on the application of EMD in periodontology, with a particular emphasis on its efficacy in addressing alveolar bone defects, peri-implantitis, and related conditions. Furthermore, this review examines the influence of EMD on the proliferation and differentiation of periodontal ligament stem cells, bone marrow stem cells, osteoblasts, and fibroblasts. It also assesses the secretion of various growth factors, including transforming growth factor-β1 (TGF-β1), bone morphogenetic protein-2 (BMP-2), collagen type 1 (COL-1), runt-related transcription factor 2 (RUNX2), and osteocalcin (OCN). Additionally, the review seeks to identify the optimal concentration for EMD application. Collectively, the studies reviewed herein suggest that EMD significantly enhances the proliferation and differentiation of relevant cellular components. The optimal concentration of EMD varies by environment and cell type. In minimally invasive periodontal surgery for intrabony defects, EMD enhances periodontal health, gingival recession coverage, and bone filling. It also benefits open-flap debridement and non-surgical treatments. However, EMD offers no extra benefits for Class II furcation defects. In treating gingival recession with coronally advanced flap (CAF) and subepithelial connective tissue graft (SCTG), EMD significantly boosts root coverage, but not with the modified coronally advanced tunnel (MCAT) technique or the semilunar coronally advanced flap. EMD's anti-inflammatory and immunomodulatory properties reduce inflammation around implants. This review indicates that EMD shows potential for periodontal regeneration, but more randomized clinical trials are necessary to assess its effectiveness.